Absorption of Amino Acids and Peptides in a Child with a Variant of Hartnup Disease and Coexistent Coeliac Disease. Issue 255 (October 1972) - Tarlow, M. J.; Seakins, J. W. T.; Lloyd, June K.; Matthews, D. M.; Cheng, B.; Thomas, A. J.
Abstract : A child with a variant of Hartnup disease and co-existent coeliac disease is described. Oral tolerance tests with L-histidine, L-tyrosine, and glycyl-L-tyrosine, and in vitro uptake studies on a small intestinal biopsy with L-histidine and glycyl-L-histidine, showed impaired absorption of the free amino acids, and showed that absorption of tyrosine and mucosal uptake of histidine was better from the dipeptides than from the free amino acids. This supports the hypothesis that the intestinal mucosa can take up small peptides intact, and that the peptide uptake mechanism is not involved in the intestinal defect of Hartnup disease.